(untitled) (Global Journal of Medical Research, 2018)
The herniation of a gravid uterus through a diverification of recti is a very rare occurrence. It may lead to some serious complications, such as incarceration and subsequent strangulation of the gravid uterus. Here we report a case of herniation of gravid uterus as a content of the anterior abdominal wall hernia secondary to diverification of recti, in a woman with previously normal delivered child.